The ultimate book of mind maps : unlock your creativity, boost your memory, change your life - Buzan, Tony.; Abbott, Susanna (London : Thorsons, 2005)
With colour illustrations throughout, this definitive guide to mind mapping is packed full of thinking tools and practical mind map examples, including running a meeting, preparing for an interview, starting up a new venture, planning family events, shopping for gifts, designing a garden, and writing a speech for a wedding.
Keywords: Thought and thinking; Intellect; Mnemonics; Note-taking.; Psychology